Using pregnancy-associated glycoproteins to provide early pregnancy diagnosis in Nelore cows - Braganca, Glaucia Mota; Monteiro, Bruno Moura; Albuquerque, Rodrigo dos Santos; Souza, Damazio Campos de [UNESP]; Campello, Claudio Cabral; Zimmerman, Silvia Oliveira; Melo, Waldjanio de Oliveira; Maia Teixeira, Pedro Paulo; Ribeiro Filho, Jose Dantas; Viana, Rinaldo Batista (Elsevier B.V., 2018)
Pregnancy-associated glycoproteins (PAG) are expressed in the placenta of ungulate mammals. Ruminants secrete PAGs continuously from embryonic implantation until delivery. In this study, we evaluated the feasibility of using ELISA to detect PAG levels as a method for early pregnancy diagnosis in Zebu (Nelore) beef cows. We compared the efficacy of this method with transrectal ultrasonography (US) in detecting pregnancy on the 25th and 28th days after timed artificial insemination (TAI) of 130 crossbred Zebu cows. Blood samples were taken during these two time points for PAG determination; ultrasound examinations were also performed on both days. Rectal palpation was used on the 80th day to definitively verify pregnancy. PAG ELISA accuracy was equal across both time points, with 100% sensitivity, 92.86% specificity, 96.70% positive predictive value, and 100% negative predictive value. In contrast, US had 62.50% and 93.18% sensitivity, 95.24% specificity, 96.49% and 97.63% positive predictive value, coupled with 54.79% and 86.96% negative predictive value on the 25th and 28th days, respectively. Thus, the two diagnosis methods differed significantly in negative predictive value and sensitivity, but not positive predictive value or specificity. In conclusion, PAG ELISA was just as specific as US, but more sensitive. Its safety (compared with US and rectal palpation) and high accuracy in identifying nonpregnant cows make PAG ELISA a good option for early pregnancy diagnosis (beginning 25 days post-TAI) in Zebu females.
Keywords: Pregnancy detection; Beef cattle; Pregnancy-associated glycoproteins; ELISA